PENGEMBANGAN COCOHIDRO (BONSAI KELAPA HIDROPONIK) SEBAGAI ALTERNATIF BISNIS BARU - Luh Ketut Sri Widhiasih; Putu Sukma Asih; Komang Ayu Nadi Hartati; Made Puspitasari; Yolanda Indriani Laja; Ni Kadek Eca Risma (Lembaga Penelitian dan Pemberdayaan (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2019)
CocoHidro is a trademark engaged in the development and sale of bonsai with coconut plant species that use hydroponic planting techniques using water as its growing medium. CocoHidro has its own uniqueness compared to other types of bonsai because CocoHidro uses coconut plants which generally grow up to dozens of meters, but in the process of making CocoHidro the coconut plants are dwarfed by regular cutting of shoots carried out by trained, trained staff. so that it will produce a type of mini coconut tree that suits your wants and needs, which in the future the dwarfed coconut seedlings will be cleaned from the coconut fibers first before proceeding with hydroponic planting. The goal to be achieved from the manufacture of CocoHidro itself is to achieve a unique business opportunity for hydroponic coconut bonsai which can compete in the market and make a profit. CocoHidro has the opportunity to be popular in the market. This is because the products are unique and have artistic value. In contrast to most bonsai plants that use plants and planting media that are already common on the market.